2015
DOI: 10.1111/echo.12883
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Bone Marrow Mononuclear Cells Delivered through a Graft Vessel for Patients with Previous Myocardial Infarction and Chronic Heart Failure: An Echocardiographic Study of Left Atrium Function

Abstract: The improvement of LA function in CABG + BMMNC group is better than CABG group. 2D strain imaging is a more sensitive tool to evaluate LA function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Among this, 306 were screened out after reviewing the title and abstract, the remaining 44 studies were screened for further full-text assessment. As four articles were from the same cohort, we selected 1 trial 21 that contained most of the parameters and combined other secondary parameters in the rest of the articles. Citation search identified 65 studies.…”
Section: Resultsmentioning
confidence: 99%
“…Among this, 306 were screened out after reviewing the title and abstract, the remaining 44 studies were screened for further full-text assessment. As four articles were from the same cohort, we selected 1 trial 21 that contained most of the parameters and combined other secondary parameters in the rest of the articles. Citation search identified 65 studies.…”
Section: Resultsmentioning
confidence: 99%
“…There were 2 relevant randomized controlled trials identified after researching the reference list of relevant literature (n = 2). These 4 literature [ 13 , 31 33 ] reports one trial. The final analysis included 22 independent RCTs [ 4 24 , 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the mean and SD of the LVEF BMSC change and LVEF control change were not directly reported by certain studies (3,5,6,9,10,12,13,15,16). The mean of the LVEF BMSC change and LVEF control change may be easily obtained by calculating the difference between the means of the LVEF baseline and LVEF follow-up .…”
Section: Methodsmentioning
confidence: 96%
“…Several previous meta-analyses on CABG combined with BMSC therapy either had certain methodological limitations or included an insufficient number of studies (2022). In addition, since the publication of those meta-analyses, several new randomized controlled trials (RCTs) have been published (3,13,15). Hence, the present meta-analysis was performed to re-evaluate the effectiveness of CABG combined with BMSC therapy.…”
Section: Introductionmentioning
confidence: 99%